The Use of Online-based Acceptance and Commitment Therapy (e-ACT) to Improve the Psychological Wellbeing among University Students - Yoke Yong, Chen; Siti Meriyam, Bakar; Rosalia, Saimon; Razitasham, Safii (Taylor & Francis, 2022)
A notable deterioration in mental health, especially anxiety and depression, was seen among university students during the Covid-19 pandemic. Therefore, immediate preventive action is required to remedy this concern by using the online-based Acceptance and Commitment Therapy (e-ACT). The effectiveness of this e-ACT on psychological flexibility and mental wellbeing was assessed among 52 Malaysian undergraduate university students aged between 18 and 23 years old during the pandemic. Based on a small group approach, participants received two online e-ACT sessions (a total of 5 hours). The paired sample t-tests result showed a significant improvement on mindfulness, psychological flexibility, and wellbeing among the students. The Wilcoxon Signed Rank Test showed a significant decrease in depression, anxiety, and stress. These findings support the use of e-ACT mental health education to promote psychological wellbeing among university students. Further empirical studies are needed to test the effectiveness of e-ACT on psychological flexibility and mental wellbeing.